Innovative Entrepreneurship: A Source of Economic Growth in the Region - Andreeva, Elena Leonidovna; Simon, Hermann; Karkh, Dmitry Andreyevich; Glukhikh, Pavel Leonidovich (Economy of Regions, 2016)
This article presents the findings of the study on the role of innovative entrepreneurship in the regional economy. The analysis is based on the methodology developed by Hermann Simon, a German scientist who has coined the term ''hidden champions” describing the phenomenon of little-known successful companies that act as innovative growth engines in the German economy. Today, the economies in different countries are developing amid the ”new normal,” in which no expected recovery followed the global crisis of2008. This makes it necessary to rethink the role of entrepreneurship during a prolonged recession. The authors proposed and tested the hypothesis that, in this environment, the economic growth in the country and the region is increasingly determined not so much by large businesses, but by many small innovative companies. To identify Russian ”hidden champions,” we studied more than 1247 companies listed in the Innovation and Investment Market, a specialized section of the Moscow Exchange, and included in the specialized Register of Business Entities that use nanotechnology. We identified specifically Russian features of innovative entrepreneurship related to national cultural and historical characteristics and the current policy of import substitution. The authors proposed their own method for assessing the innovative entrepreneurship as a source of economic growth in the Russian regions that defines five groups of innovative entrepreneurs (global market leader, one of the global market leaders, Russian market leader, one of the Russian market leaders, not the leader in the Russian market) and compares them with large companies in terms of turnover and profit dynamics. Based on such criteria as ''number of ''hidden champions” and ''number of large enterprises per 100 thousand organizations,” we built a model for the ratio of ''hidden champions” to major companies in the Russian regions that identifies, for each criterion, three subgroups, including leaders, medium-tier and outsiders, which allowed to identify nine types of Russian regions and substantiate different development strategies for main types of regions. The study confirms that the most justified strategy for the development of innovative entrepreneurship in the region is the strategy of cooperation between different types of companies in order to overcome their weaknesses, enhance existing opportunities and activate the innovation and entrepreneurial capacity.